2001
DOI: 10.1191/096032701682693035
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparison of the cytotoxicity of sulphur mustard in melanoma and keratinocyte cell lines

Abstract: In vivo, the pigment producing melanocytes are the most susceptible cell type to sulphur mustard (HD) in the epidermal region of pig skin. It has been postulated that this is due to the melanogenic pathway producing a cytotoxic, free radical cascade within the melanocyte following HD poisoning, leading to cellular necrosis and subsequent inflammation. To test this hypothesis, the cytotoxicity of HD was tested in three human melanoma cell lines and compared to SVK-14 human keratinocytes, a cell line in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…These findings are consistent with Smith et al (2001), who also showed that G361 cells were more resistant than SVK14 cells to the effects of H 2 O 2 to a similar extent, alluding to related resistance mechanisms involving an upregulated DNA repair capacity. In the present study, differences in cell population growth rates alone could not account for the greater sensitivity of SVK14 cells to HD, because despite the known deleterious effects of HD on rapidly dividing cells (Maynard, 1987) the G361 cell cultures were found to have a higher growth rate than SVK14 cell cultures.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with Smith et al (2001), who also showed that G361 cells were more resistant than SVK14 cells to the effects of H 2 O 2 to a similar extent, alluding to related resistance mechanisms involving an upregulated DNA repair capacity. In the present study, differences in cell population growth rates alone could not account for the greater sensitivity of SVK14 cells to HD, because despite the known deleterious effects of HD on rapidly dividing cells (Maynard, 1987) the G361 cell cultures were found to have a higher growth rate than SVK14 cell cultures.…”
Section: Discussionsupporting
confidence: 92%
“…The results confirm previous findings by Smith et al (2001), who found that cellular proliferation in G361 cultures could recover following HD exposure, although in the present study this was not evident at HD doses of >60 µM. This is suggestive of a limited repair capability and would explain the markedly greater resistance of G361 cells at 72 h compared with SVK14 cells, significant differences in cell culture viability being found at 20, 30 and 60 µM HD.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…One-dimensional SDS PAGE and Western blotting were carried out as described in reference [14]. The cell fractions were diluted with Laemmli sample buffer (Bio-Rad Laboratories Ltd., Hemel Hempstead, UK) to the required protein concentration and then heated at 100 • C for 5 min.…”
Section: Gel Electrophoresis and Western Blottingmentioning
confidence: 99%